A Comparative Analysis of Students Technology Uses During Covid-19 Lockdown in Ghana - Aboagye, Caroline D.; Opoku, Eric M.; Agyepong, Lawrencia (Covenant Journal of Communication, 2021)
The study tests an author-derived quantitative version of the Student Technology Use Framework by assessing the effectiveness of distance learning technologies deployed by universities in Ghana during the Covid-19 lockdown period. It focuses on the knowledge acquisition needs of students who were initially admitted into the traditional learning mode but had to adapt to distance learning following the lockdown. The population comprises undergraduate and postgraduate students of the Christian Service University College (CSUC), a private university in Kumasi, and the Ghana Institute of Journalism (GIJ), a public university in Accra. The sample size was 351 - 187 from CSUC and 164 from GIJ. Copies of a questionnaire were distributed to CSUC students by personal contact, and a Google Forms link to GIJ students via e-mail. Results show that students in public universities had lower technological learning capabilities than their compatriots in private universities, resulting in a better learning experience throughout the lockdown